PERANCANGAN VIDEO CINEMATIC “TITIK BALIK” SEBAGAI MEDIA PROMOSI SOFT SELLING UNTUK BEBERRRSIH SALATIGA - Slyvester Rodrigo Pay; Birmanti Setia Utami; Martin Setyawan (Universitas Negeri makassar, 2025)
Beberrrsih Salatiga is an environmental community focused on education and real actions in waste management. To expand its message reach without direct promotional approaches, a cinematic video titled Titik Balik was designed as a softselling promotional medium. This research aims to create an audiovisual media that conveys Beberrrsih’s core values emotionally through a personal narrative. The methods used include observation, interviews, and literature studies, followed by stages of pre-production, production, and post-production. The final product is a 5-minute video featuring cinematic visuals, a reflective narrative, and warm color tones that portray the transformation of a character as a symbol of behavioral change. Evaluation by the resource person concluded that the media is sufficiently effective in representing the community’s identity. The video is ready for publication on social media as an initial step of implementation.